Association between cancer‐specific adverse event triggers and mortality: A validation study. (13th April 2020) - Weingart, Saul N.; Nelson, Jason; Koethe, Benjamin; Yaghi, Omar; Dunning, Stephan; Feldman, Albert; Kent, David; Lipitz‐Snyderman, Allison
Abstract: Background: As there are few validated measures of patient safety in clinical oncology, creating an efficient measurement instrument would create significant value. Accordingly, we sought to assess the validity of a novel patient safety measure by examining the association of oncology‐specific triggers and mortality using administrative claims data. Methods: We examined a retrospective cohort of 322 887 adult cancer patients enrolled in commercial or Medicare Advantage products for one year after an initial diagnosis of breast, colorectal, lung, or prostate cancer in 2008‐2014. We used diagnosis and procedure codes to calculate the prevalence of 16 cancer‐specific "triggers"–events that signify a potential adverse event. We compared one‐year mortality rates among patients with and without triggers by cancer type and metastatic status using logistic regression models. Results: Trigger events affected 19% of patients and were most common among patients with metastatic colorectal (41%) and lung (50%) cancers. There was increased one‐year mortality among patients with triggers compared to patients without triggers across all cancer types in unadjusted and multivariate analyses. The increased mortality rate among patients with trigger events was particularly striking for nonmetastatic prostate cancer (1.3% vs 7.5%, adjusted odds ratio 1.96 [95% CI 1.49‐2.57]) and nonmetastatic colorectal cancer (4.1% vs 11.7%, 1.44 [1.19‐1.75]). Conclusions: The association between adverse event triggers and poor survival among a cohort of cancer patients supports the validity of a cancer‐specific, administrative claims‐based trigger tool. Abstract : In a retrospective longitudinal cohort of 322 887 newly diagnosed patients with breast, colorectal, lung, or prostate cancer, there was increased one‐year mortality among patients who experienced oncology‐specific claims‐based triggers compared to patients without triggers. Increased mortality was observed across all cancer types, stratified by metastatic status, in unadjusted and multivariate analyses.